Identifying missing pieces in color vision defects: a genome-wide association study in Silk Road populations - Nardone, Giuseppe Giovanni; Spedicati, Beatrice; Concas, Maria Pina; Santin, Aurora; Morgan, Anna; Mazzetto, Lorenzo; Battaglia-Parodi, Maurizio; Girotto, Giorgia (Frontiers in Genetics, 2023)
Introduction: Color vision defects (CVDs) are conditions characterized by the alteration of normal trichromatic vision. CVDs can arise as the result of alterations in three genes (OPN1LW, OPN1MW, OPN1SW) or as a combination of genetic predisposition and environmental factors. To date, apart from Mendelian CVDs forms, nothing is known about multifactorial CVDs forms. Materials and Methods: Five hundred and twenty individuals from Silk Road isolated communities were genotyped and phenotypically characterized for CVDs using the Farnsworth D-15 color test. The CVDs traits Deutan-Protan (DP) and Tritan (TR) were analysed. Genome Wide Association Study for both traits was performed, and results were corrected with a False Discovery Rate linkage-based approach (FDR-p). Gene expression of final candidates was investigated using a published human eye dataset, and pathway analysis was performed. Results: Concerning DP, three genes: PIWIL4 (FDR-p: 9.01*10-9), MBD2 (FDR-p: 4.97*10-8) and NTN1 (FDR-p: 4.98*10-8), stood out as promising candidates. PIWIL4 is involved in the preservation of Retinal Pigmented Epithelium (RPE) homeostasis while MBD2 and NTN1 are both involved in visual signal transmission. With regards to TR, four genes: VPS54 (FDR-p: 4.09*10-9), IQGAP (FDR-p: 6,52*10-10), NMB (FDR-p: 8.34*10-11), and MC5R (FDR-p: 2.10*10-8), were considered promising candidates. VPS54 is reported to be associated with Retinitis pigmentosa; IQGAP1 is reported to regulate choroidal vascularization in Age-Related Macular Degeneration; NMB is involved in RPE homeostasis regulation; MC5R is reported to regulate lacrimal gland function. Discussion: Overall, these results provide novel insights regarding a complex phenotype (i.e., CVDs) in an underrepresented population such as Silk Road isolated communities.